Study on the Frosting Characteristics of Bare Copper Surface UnderWeak Alternating Magnetic Field - Meng Yu; Liu Bin; Shan LiangLiang; Zhang Rui; Chen Aiqiang; Georges EL ACHKAR; Bennacer Rachid (Zhileng xuebao, 2020)
In this paper, the frosting at a bare copper cold plate in a natural convective environment were studied. The temperature and relative humidity of the inflowing air were 25 °C and 49%, respectively, and the copper plate was maintained at -20 °C.An AC magnetic field with the strengths of 2.0×10-3, 2.5×10-3, 3.0×10-3, 3.5×10-3, 4.0×10-3, 4.5×10-3, 5.0×10-3, 5.5×10-3, and 6.0×10-3 T were applied to the frosting process. The results showed that thesupercooling degree of the crystals increased, but the driving force fornucleation decreased when magnetic field existed. Compared with the absence of a magnetic field, the droplet condensation time and the droplet size were reduced. Visualization studies demonstrated that the polar water molecules were arranged in the bottom plate in an orderly manner, the system’s entropy was reduced, and the driving force for crystallization was increaseddue to the additional magnetic field. The time to form a dense frost layer was reduced by 6%. In addition, with increased magnetic field strength, the amount of frost per unit area of the plate decreased under a weak AC magnetic field. A high correlation of the amount of frost deposited with the AC magnetic field strength was apparent and the fitted relationship was given in the paper.